Identificación de fructooligosacáridos e inulinas en residuos de hojas de fique -Furcraea macrophylla Baker (2015)
Colombia is the largest producer of cabuya, natural fiber extracted from fique (Furcraea macrophylla Baker). The fique exploitation is characterized by traditional products and processes, low-tech, low value-added and limited plant use, resulting in low profitability. However, residues of this agroindustrial process contain many substances of interest, unexplored yet, including carbohydrates, specifically fructans, such as inulin and fructooligosaccharides which are fructose polymers that are considered dietary fiber and for their characteristics are classified as prebiotics. Through enzymatic and spectrophotometric techniques, in this research is evidenced the presence of FOS and inulin in the residues obtained during the fique leafs defibrating process. Given the wide applications in the food industry, quantification, extraction and characterization is recommended in order to provide added value through the exploitation of these compounds.